Atividade de morcegos em cinco hábitats de uma paisagem fragmentada de Floresta Atlântica do sul do Brasil - Suckow, Urubatan Moura Skerratt [UNESP] (2014)
We investigated the foraging activity of bats in five habitats in an Atlantic Forest landscape located in southern Brazil. Using mist-nets and ultrasound detectors, we tested the two hypotheses (Chapter I): (a) phyllostomids activity is highest in conserved forests than in degraded habitats (riparian area, city and monoculture); (b) aerial insectivorous activity (molossids and vespertilionids) is highest in open space habitats (city, riparian degraded area and monoculture) than narrow space habitats (submontane and riparian forest). The first hypothesis was confirmed, but the abundance and richness were similar in degraded riparian areas and conserved forests. Moreover, aerial insectivorous bats (molossids and vespertilionids) were more active in open habitats especially in the urban environment and degraded riparian areas supporting the second hypothesis. Using the same methods (mist-nets and ultrasound detectors), we evaluated (Chapter II) the “lunar phobia” on aerial insectivorous (molossids and vespertilionids) and frugivorous phyllostomids, considering the prediction that activity of the insectivorous are independent of the brightness of the moon (faster aerial foragers) while frugivorous are less activity during periods of more brightness (slowest foragers). The results indicated response variation related to the brightness just to phyllostomids, confirming the initial prediction. The data set for this dissertation demonstrates that four common phyllostomids (Artibeus lituratus, A. fimbriatus, Carollia perspicillata, Sturnira lilium) explore different environments in the region, including open plots as degraded riparian areas. These places seem to favor the activity not only some phyllostomids but also aerial insectivorous bats (molossids and vespertilionids) as sites to movement between forest patches or feeding areas. The variation in foraging activity of insectivorous and frugivorous phyllostomids seems related with the ...